Hagelgefährdung und Hagelrisiko in Deutschland basierend auf einer Kombination von Radardaten und Versicherungsdaten - Schmidberger, Manuel (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2018)
This work presents a new approach for a hail loss model to quantify the hail risk on residual buildings for high return periods. Based on the analysis of 3D radar data from 2005 to 2015 a stochastic hail track model is developed to sample a random number of stochastic hail tracks. A detailed vulnerability analysis combines the hazard from the hail tracks and the vulnerability of buildings towards hail and leads to the hail risk for a certain portfolio.